Escribimos recetas saludables - Garcia Panta, Rosa Elvira (2018)
In accord to the provisions for the Education Faculty to the National University of Trujillo, in the Academic Grades and Titles to get the Bachelor’s degree in Elementary Education, I leave for consideration the present design to the activities learning in the communication area for the fourth elementary grade , called: "We write healthy recipes", considering that, as a teacher, I have the responsibility to offer students a formation for life ,developing the writing authentic competence and functional texts, from real situations. In this porpose, integrating and motivating, I hope, it represents a firm step in the strengthening to the students' written expression, a skill that will increase their success in the textual production, expecting from you - if it is the case - the guidelines that will strengthen my training in the service in the pedagogical practice. So much so that, in this research, theoretical and pedagogical support are integrated, resulting in systematization, considering that healthy eating implemented in recipes consumed by students in schools will improve the vitamin deficiency in their bodies, which will lead to improved learning. A well-nourished student, a successful student.